Development of the Tampa Scale of Kinesiophobia for Parkinson's disease. Issue 2 (June 2015) - Monticone, Marco; Ferrante, Simona; Ambrosini, Emilia; Rocca, Barbara; Secci, Claudio; Foti, Calogero
<x xml:space="preserve">Abstract</x> The aim of this study was to validate the Tampa Scale of Kinesiophobia for Parkinson's disease (TSK-PD). This was a cross-sectional evaluation of the psychometric properties of an adapted questionnaire. The psychometric testing included confirmatory factor analysis, reliability by internal consistency (Cronbach's α) and test–retest reliability (intraclass correlation coefficient), construct validity by comparing TSK-PD with the Falls Efficacy Scale-International (FES-I), the Movement Disorder Society – Unified Parkinson's Disease Rating Scale (MDS-UPDRS), the Hospital Anxiety and Depression Score (HADS) and the Short-Form Health Survey (SF-36) (Pearson's correlations), and sensitivity to change by calculating the smallest detectable change. The questionnaire was administered to 132 patients with Parkinson's disease. Factor analysis confirmed a two-factor (harm and activity avoidance), 13-item solution, which led to an acceptable data-model fit. Internal consistency (α=0.94) and test–retest reliability (intraclass correlation coefficient, model 2.1=0.90) were good. Construct validity showed a close correlation between the TSK-PD and FES-I (r=−0.710); a moderate correlation with the MDS-UPDRS (r=0.513); moderate to close correlations with HADS-D (r=0.443) and HADS-A (r=0.626); moderate correlations with the mental subscales of the SF-36 (r=−0.327 to −0.563); and poor correlations with the physical subscales of the SF-36 (r=−0.236 to −0.248). The smallest detectable change was 11. The TSK-PD had a good factorial structure and satisfactory psychometric properties. Its use is recommended for clinical and research purposes.